Optimization of lipase-catalyzed esterification for the production of medium-chain acylgcerols from palm oil fatty acid distillate: using response surface methodology - Mohd Dom, Zanariah; Ling, Tau Chuan; Yusoff, Rozita (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Optimization of lipase-catalyzed esterification for the production of medium-chain acylglycerols (MCA) from palm oil fatty acid distillate (PFAD) and glycerol was carried out in order to determine the factors that have significant effects on the reaction system and MCA yield. Oil palm mesocarp lipase was used as catalyze in the esterification reaction. Response surface methodology (RSM) was applied to optimize the reaction conditions. The reaction conditions, namely, the reaction time (30-240 min), enzyme load (0.5-1.5kg), silica gel load (0.2-1.0 kg), and solvent amount (200-600 vol/wt). Reaction time, enzyme loading and solvent amount strongly effect MCA synthesis (p<0.05). However, water absorbent (silica gel) loading did not have significant (p>0.05) influence on MCA yield. Best-fitting models were successfully established for MCA yield (R2 =0.9133). The optimum MCA yield were get 75% by prediction and 75.4% by experimental run by using 6kg enzyme loading, a reaction time of 135min and a solvent amount of 350 vol/wt at 65oC reaction temperature.. Verification experiments under optimized reaction conditions were conducted, and the results agreed well with the range of predictions.